The Role of Women in Medical Services in the Early Islamic Period - Ozturk, Levent (European Journal of Multidisciplinary Studies, 2016)
During the time of the Prophet Muhammad, some women took part in medical services to contribute their society, in Mecca and Medina. We found approximately 50 women contributing to their society in terms of medical services. Their medical contributions were generally traditional practices about the daily necessities of their society. Understanding the service provided by these women to their society at that time is very significant in terms of its contribution to the history of folk medicine. The contribution of these women was mainly in the areas of the nursing and assisting the midwifes, prenatal and postnatal care, some surgical operations, caring were wounded in wars, giving soldiers a meal, medical treatment for some diseases and daily injuring, treatment of animal beats, psychological therapy, practicing dietician care and body care, some folkloric treatments of some pediatric diseases, and sexual education. In this paper, I will ground my work on Islamic sources.